Direct fermentation of potato starch to ethanol by cocultures of Aspergillus niger and Saccharomyces cerevisiae. - Abouzied, M M (1986)
Direct fermentation of unhydrolyzed potato starch to ethanol by monocultures of an amylolytic fungus, Aspergillus niger, and cocultures of A. niger and Saccharomyces cerevisiae was investigated. Amylolytic activity, rate and amount of starch utilization, and ethanol yields increased several-fold in coculture versus the monoculture due to the synergistic metabolic interactions between the species. Optimal ethanol yields were obtained in the pH range 5 to 6 and amylolytic activity was obtained in the pH range 5 to 8. Ethanol yields were maximal when fermentations were conducted anaerobically. Increasing S. cerevisiae inoculum in the coculture from 4 to 12% gave a dramatic increase in the rate of ethanol production, and ethanol yields of greater than 96% of the theoretical maximum were obtained within 2 days of fermentation. These results indicate that simultaneous fermentation of starch to ethanol can be conducted efficiently by using cocultures of the amylolytic fungus A. niger and a nonamylolytic sugar fermenter, S. cerevisiae.